2015
DOI: 10.5268/iw-5.3.815
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus transport by the largest Amazon tributary (Madeira River, Brazil) and its sensitivity to precipitation and damming

Abstract: Phosphorus transport by the largest Amazon tributary (Madeira River, Brazil) and its sensitivity to precipitation and damming. AbstractOriginating in the Bolivian and Peruvian Andes, the Madeira River is the largest tributary of the Amazon River in terms of discharge. Andean rivers transport large quantities of nutrient-rich suspended sediments and are the main source of phosphorus (P) to the Amazon basin. Here, we show the seasonal variability in concentrations and loads of different P forms (total, particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 37 publications
2
22
1
Order By: Relevance
“…P occurs as dissolved and particulate inorganic and organic forms. In the present study, P was mainly in particulate form, similarly to other turbid rivers (Almeida et al, 2015;Pedrozo & Bonetto, 1987). A substantial part of the PP carried by the Middle Paraná River is deposited in floodplain lakes during high waters (Maine et al, 2004).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…P occurs as dissolved and particulate inorganic and organic forms. In the present study, P was mainly in particulate form, similarly to other turbid rivers (Almeida et al, 2015;Pedrozo & Bonetto, 1987). A substantial part of the PP carried by the Middle Paraná River is deposited in floodplain lakes during high waters (Maine et al, 2004).…”
Section: Discussionsupporting
confidence: 80%
“…of P by acting as storage sites for particles (González-Sanchis, Murillo, Cabezas, Vermaat, & Comín, 2015;Kiedrzyńska et al, 2008;Maine, Suñe, & Bonetto, 2004). In contrast, other authors have shown that floodplains are P sources due to the exportation of the dissolved fraction (Almeida et al, 2015;Fisher & Acreman, 2004;Reavis & Haggard, 2016). The spatial dynamics of P also shows variable trends; while some studies have shown an increasing concentration from the main channel (MC) to the floodplain (Roberto, Santana, & Thomaz, 2009;Villar, de Cabo, Vaithiyanathan, & Bonetto, 1999); other studies have shown the opposite (González-Sanchis et al, 2015;Maine et al, 2004).…”
mentioning
confidence: 96%
“…), and the climate is humid tropical, with mean annual precipitation of about 2000 mm (Moreira‐Turcq et al ). This high annual precipitation is unevenly distributed across the year (Villar et al ), so that discharges in the Madeira River can vary by one order of magnitude between low and high waters, averaging 19,000 m 3 s −1 at Porto Velho (Almeida et al ) and 31,000 m 3 s −1 at the mouth (Moreira‐Turcq et al ). The Bolivian plain, after the headwater tributaries exit the Andes, is characterized by the occurrence of large wetlands.…”
Section: Methodsmentioning
confidence: 99%
“…River, the largest source of water, sediments, and nutrients to the Amazon River mainstem (McClain and Naiman, 2008;Almeida et al, 2015).…”
Section: Introductionmentioning
confidence: 99%